How Can Personas Support Online Advertising Process? Proposing ‘Persona-Based Online Advertising Optimization - Kaate Ilkka; Salminen Joni; Jung Soon-Gyo; Olkkonen Rami; Jansen Bernard (Belgium, 2025)
Personas represent different kinds of users belonging to a particular demographic, behavior, and/or attitude group. Personas supposedly bring customers closer to marketing management. Personas have been used in marketing for decades but their potential in online advertising optimization is still to be shown. In this research, we determine what an online advertising process (OAP) is and we propose a model for Persona-based online advertising optimization (PbOAO) to conceptually examine personas’ value in each step of the OAP. We conclude by proposing next steps for empirical testing of the PbOAO model.
Proceedings of the European Marketing Academy, 52nd, EMAC 2023 Annual